Pengaruh Gaya Kepemimpinan, Kerjasama Tim, Disiplin Kerja Terhadap Kinerja Karyawan PT. Wana Citra Sentosa - Yunita Maulinda; Alfiyani Rizkha Ayu; Dimas Tri Meityas Pamungkas; Fendi Arya Krisdianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Employee performance is the main key in a company. Employee performance is influenced by several factors, including leadership style, teamwork, work discipline. This research aims to determine the influence of leadership style, teamwork, work discipline at PT Wana Citra Sentosa. This type of research is research using quantitative research methods. The population determined in this research is employees at PT Wana Citra Sentosa, totaling 54 people. In sampling, the technique used is the Probability Sampling technique using a simple random sampling technique. The data collection method is the analysis method, namely the multiple linear regression method. The data was processed using SPSS (Statistical Program for Social Science ) version 25. The research results showed that the independent variables leadership style, teamwork, work discipline had a positive and significant effect on the dependent variable employee performance at PT Wana Citra Sentosa